The Relationship Between Pregnancy Discomfort and Physical Activity of Third Trimester Pregnant Women - Yanti Srinayanti; Sri Anggraeni; Resna Litasari; Lilis Lismayanti (LPPM STIKes Muhammadiyah Ciamis, 2023)
Purpose: This study aims to determine the relationship between discomfort in pregnancy and the physical activity of third-trimester pregnant women. Methods: quantitative analytic survey with a cross-sectional research design. The population in this study was 23 third-trimester pregnant women in Banjaranyar Village. Sampling in this study used a total sample of 23 respondents. Results showed that the age of the majority of respondents was reproductive age (20-35 years), 56.5%, and most respondents had low education, namely 16 respondents, for a total of 69.6%. The frequency of parity of the majority of respondents is primipara, namely having given birth. There are as many as 10 respondents, for a total of 43.5%. Of the 23 respondents, the frequency of pregnant women feeling discomfort was 21 respondents (91.3%), pregnant women did light activities as many as 18 respondents (78.3%). Conclusions: There is a relationship between discomfort in pregnancy and the physical activity of pregnant women in Banjaranyar Village, Banjaranyar District.